Clinical course of patients with incidental finding of 20q‐ in the bone marrow without a morphologic evidence of myeloid neoplasm. Issue 6 (6th April 2016) - Jawad, Majd D.; Shi, Min; Oliveira, Jennifer L.; Hoyer, James D.; Christopher Hook, C.; Go, Ronald S.
Abstract : Deletion of the long arm of chromosome 20 (20q‐) is a frequent finding in bone marrow karyotypes, mainly associated with myeloid neoplasms (MNs). Its clinical significance in the setting of normal bone marrow morphology is unclear. We described the clinical characteristics, cytogenetic findings, and outcome of 102 such patients seen at our institution from 2000‐2014. Their median age was 66 years. The indication for bone marrow biopsy was either unexplained cytopenias (48%) or hematologic cancer staging/reevaluation (52%). In 88 (86%) patients, 20q‐ was an isolated finding. Thirty‐nine (38%) patients previously received chemotherapy and 88 (86%) had cytopenias at the time of 20q‐ finding. After a median of 35 months, 12 (13%) patients developed MNs: 10 myelodysplastic syndromes, one acute myeloid leukemia and one myeloproliferative neoplasm. None of 14 patients with normal blood counts, but 7 of 35 (20%) with mild cytopenias, and 5 of 53 (9%) with moderate/severe cytopenias developed MNs. We did not find an association between the number of metaphases with 20q‐ and the development of MN. The incidental finding of 20q‐ in the bone marrow generally does not portend an early stage MN. Particularly, those without cytopenias at the time of diagnosis may have a good prognosis. Am. J. Hematol. 91:556–559, 2016. © 2016 Wiley Periodicals, Inc.